South west region infection prevention and control network. Issue 2 (1st September 2011) - Stevens, Alison
Abstract : The Hospice Nurse Managers in the South West have worked collaboratively to develop a SW regional hospice network for Infection Prevention and Control. Initially it was agreed to host a launch event at Dorothy House Hospice to look at the changes in infection prevention and control at national level and how this might impact on hospices. Additionally there was open discussion on how a regional network for infection prevention and control might function and draft terms of reference were prepared. At the second meeting the terms of reference were agreed in addition to a range of topics that might be included at regional meetings, a list of suitable dates and ownership by hospices for hosting meetings. Challenges have included how this network might link to local PCT or Health Protection Agency initiatives/events, the varying levels of infection prevention and control already operating within hospices and meeting national requirements as small organisations. Benefits so far have included the opportunity to work collaboratively with other hospices on infection prevention and control issues, learning from each other and sharing experience and good practice. South West Region Forum for Hospice Nurse Managers. March 2011.